Relationship between economic freedom and pro-poor growth: Evidence from Pakistan (1995-2010) - Khalid Zaman; Muhammad Mushtaq Khan; Mehboob Ahmad (Romanian Journal of Fiscal Policy (RJFP), 2011)
The relationship between economic freedom and pro-poor growth is examined in Pakistan from 1995-2010. The concept of pro-poor growth is derived from the literature of Kakwani and Pernia (2000) and Kakwani and Son (2003). The domino effect shows that there is a strong link between economic freedom indicators and pro-poor growth. Econometric analysis proves a strong relationship between economic freedom, poverty reduction and income inequality. Results reveal that larger the business freedom and / or trade freedom, greater the economic growth. This will ultimately reduce poverty in the country.
Keywords: I30; I32; O10; 330; economic freedom indicators; pro-poor growth; poverty; inequality; Pakistan